Assisted cool down procedures in high performance swimmers - Strozberg, M. V.; Klar, A. B. (Medicine & Science in Sports & Exercise, 1998)
Cool down work should be aerobic, slow movement patterns, and terminated when heart rate is less that 110-100 bpm.